Autogenous Mesenchymal Stem Cells from the Vertebral Body Enhance Intervertebral Disc Regeneration via Paracrine Interaction: An in Vitro Pilot Study. Issue 10 (October 2016) - Shim, Eun-Kyung; Lee, Jung-Seok; Kim, Dong-Eun; Kim, Seul Ki; Jung, Byung-Joo; Choi, Eun-Young; Kim, Chang-Sung
Several in vivo studies have found that transplanting mesenchymal stem cells (MSCs) into degenerative intervertebral discs (IVDs) leads to regeneration of disc cells. Since the exact underlying mechanisms are not understood, we investigated the mechanisms of action of MSCs in regeneration of degenerative IVDs via paracrine actions. Human MSCs and degenerative disc cells from the same donor vertebrae were directly or indirectly cocultured. The multidifferentiation potential, cell proliferation, collagen synthesis, and mRNA expression levels were assessed. The proliferation rates of MSCs and degenerative disc cells were higher in the coculture system than in the monolayer cultures or in the conditioned medium of each cell type. During coculturing with nucleus pulposus (NP) cells, mRNA expression of the extracellular matrix (ECM) components aggrecan, versican (VCAN), SOX9, and type II and type VI collagen was significantly increased in MSCs, whereas mRNA expression for type V collagen was increased in MSCs cocultured with annulus fibrosus (AF) cells. In addition, the accumulation of total ECM collagen was greater in cocultured degenerative disc cells than in monocultured cells. During coculturing, MSCs downregulated the expression levels of various proinflammatory cytokine genes in degenerative NP [interleukin-1α ( IL-1α ), IL-1β, IL-6, and tumor necrosis factor-α ( TNF-α )] and AF cells ( IL-1α and IL-6 ), which are involved in the degradation of ECM molecules. In association with the trophic effect of MSCs on degenerative disc cells, upregulation of growth factor mRNA expression was shown in MSCs cocultured with degenerative NP cells [epidermal growth factor ( EGF ), insulin-like growth factor-1 ( IGF-1 ), osteogenic protein-1 ( OP-1 ), growth and differentiation factor-7 ( GDF-7 ), and transforming growth factor-β ( TGF-β )] or degenerative AF cells ( IGF-1, OP-1, and GDF-7 ). In terms of MSC-based clinical approaches to IVD regeneration, implanting MSCs into a degenerative IVD may both stimulate MSC differentiation into an NP- or AF-like phenotype and stimulate the biological activation of degenerative disc cells for self-repair.